العلم و العلماء في الجزائر خلال عهد الدايات 1082هـ - 1246هـ / 1671م/ 1830م - مراحي جيهان; مراحي أميرة (My University, 2022)
Abstract: Our thesis focuses on the subject of scholars and sciences in Algeria during the period of the Ottoman rule, spanning from 1671 to 1830. It examines the various institutions of knowledge, such as the Katatib, Zaouias, and mosques, highlighting their educational and cultural role in the development of educational and cultural life in Algeria and the different stages a student must navigate during their studies. It also aims to clarify the relationship between scholars and authority, exploring both aspects of power, convergences, and divergences, while also indicating the cultural relations between the Maghreb countries and the movements of cultural leaders from different regions. We also examine the biographies and travels of these scholars, as well as their lasting impact. ----------------------------- ملخص: تركز أطروحتنا على موضوع العلماء والعلوم في الجزائر خلال فترة الحكم العثماني، الممتدة من عام ١٦٧١ إلى عام ١٨٣٠. وتتناول الدراسة مختلف مؤسسات المعرفة، كالكتاتيب والزوايا والمساجد، مسلطةً الضوء على دورها التربوي والثقافي في تطوير الحياة التعليمية والثقافية في الجزائر، والمراحل الدراسية المختلفة التي يمر بها الطالب. كما تهدف إلى توضيح العلاقة بين العلماء والسلطة، مستكشفةً جوانب القوة والتقارب والاختلاف، مع الإشارة إلى العلاقات الثقافية بين دول المغرب العربي وحركة القادة الثقافيين من مختلف المناطق. كما ندرس سير هؤلاء العلماء ورحلاتهم، بالإضافة إلى أثرهم الدائم. ----------------------------------- Résumé : Notre thèse s'intéresse au sujet des savants et sciences en Algérie durant la période du gouvernement des Days s'étendent de 1671 à 1830. On aborde les différents instituts du savoir tel que Katatib, Zaouias,et mosquées en citant leur rôle éducatif et culturel dans le développement de la vie éducative et culturelle en Algérie et les différents étapes que l'étudiant doit parcourir au cours de ses études. A aussi pour but de clarifier la relation entre les savants et l'autorité avec ses deux faces du pouvoir soi les convergences les divergences tout en indiquant les relations culturelles entre les pays du maghreb et les déplacements des leaders culturels de pans et d'autres. On s'intéresse aussi à la biographie et aux voyages de ces savants ainsi qu'à leurs empreintes.
Keywords: العلوم - العلماء - العثمانيون - الجزائر